Environment reconstruction and navigation with electric sense based on a Kalman filter. (February 2013) - Lebastard, Vincent; Chevallereau, Christine; Girin, Alexis; Servagent, Noël; Gossiaux, Pol-Bernard; Boyer, Frédéric
Electric fish sense the perturbations of a self-generated electric field through their electro-receptive skin. This sense allows them to navigate and reconstruct their environment in conditions where vision and sonar cannot work. In this article, we use a sensor inspired by this sense to address both problems of locating and estimating the size of small objects (electrolocation) and navigating in a tank. Based on a Kalman filter, any small object in the surroundings of the motion-controlled sensor can be modeled as an equivalent sphere whose location is well estimated by the filter. As a first application to the problem of navigation, the filter is included into a closed feedback loop in order to achieve wall following in a tank. Our experimental results demonstrate the feasibility of this approach.